A Notes on Matrix Sequence of Pentanacci Numbers and Pentanacci Cubes - Sivakumar, B.; James, V. (Communications in Mathematics and Applications, 2022)
Pentanacci sequence is a fifth order recurrence relation and Pentanacci cubes \(Γ_{n}^{(5)}\) are induced subgraphs of the hypercube, obtained by removing all the vertices that contain five or more consecutive 1's. In the present work, we give some properties related to matrix sequence of Pentanacci numbers and Pentanacci cubes \(Γ_{n}^{(5)}\). Also, we investigate the generating function of matrix sequence and cube polynomials of Pentanacci cubes.
Keywords: Fibonacci cube; Pentanacci cube; Pentanacci sequence; Hypercube; Matrix sequence